Munidopsis pericalla Macpherson 2007 - Baba, Keiji; Macpherson, Enrique; Poore, Gary C. B.; Ahyong, Shane T.; Bermudez, Adriana; Cabezas, Patricia; Lin, Chia-Wei; Nizinski, Martha; Rodrigues, Celso; Schnabel, Kareen E. (Zenodo, 2008)
Munidopsis pericalla Macpherson, 2007 Munidopsis pericalla Macpherson, 2007: 91, figs 43, 55K (Solomon Islands, Philippines, 135–259 m). Type data: holotype, male, MNHN-Ga 5564. Type locality: Solomon Islands, 10°12.1´S, 161°19.2´E, 135–325 m. Munidopsis petalorhyncha Baba, 2005 Munidopsis petalorhyncha Baba, 2005: 189, 292 (key, synonymies, replacement name, preceded by M. latimana Miyake & Baba, 1966). Munidopsis subsquamosa latimana Birstein & Zarenkov, 1970: 423, figs 1, 2 (Kuril Trench, 5035–5210 m). Type data: holotype, male, OIRAS. Type locality: Kuril Trench, 5035–5210 m. : Published as part of Baba, Keiji, Macpherson, Enrique, Poore, Gary C. B., Ahyong, Shane T., Bermudez, Adriana, Cabezas, Patricia, Lin, Chia-Wei, Nizinski, Martha, Rodrigues, Celso & Schnabel, Kareen E., 2008, Catalogue of squat lobsters of the world (Crustacea: Decapoda: Anomura-families Chirostylidae, Galatheidae and Kiwaidae), pp. 1-220 in Zootaxa 1905 (1) on page 154, DOI: 10.11646/zootaxa.1905.1.1, http://zenodo.org/record/5134587 : {"references": ["Macpherson, E. (2007) Species of the genus Munidopsis Whiteaves, 1784 from the Indian and Pacific Oceans and reestablishment of the genus Galacantha A. Milne-Edwards, 1880 (Crustacea, Decapoda, Galatheidae). Zootaxa, 1417, 1 - 135.", "Baba, K. (2005) Deep-sea chirostylid and galatheid crustaceans (Decapoda: Anomura) from the Indo-West Pacific, with a list of species. Galathea Reports, 20, 1 - 317.", "Birstein, J. A. & Zarenkov, N. A. (1970) On bottom decapods (Crustacea, Decapoda) of the Kurile-Kamchatka Region. In: Bogorov, V. G. (ed.), Fauna of the Kurile-Kamchatka Trench and its environment. Memoirs of the Institute of Oceanology, Academy of Sciences, U. S. S. R., 86, 420 - 426."]}